REPACKAGING: MODEL PEMBELAJARAN DISCOVERY LEARNING KE MODE ONLINE DI SEKOLAH DASAR - Rifyan Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to formulate a discovery learning model with online learning mode. This type of research is descriptive qualitative with participants consisting of 24 students and 2 teachers taken based on purposive sampling technique. The instruments used were questionnaires and unstructured interviews which were processed using triangulation techniques. The results of this study show that: 1) At the stimulation stage, teachers provide stimulation to students through zoom meetings or google meet synchronously; 2) At the problem identification stage, the teacher does it synchronously and asynchronously; 3) At the data collection stage, students asynchronously collect data using observation tables that have been provided or designed by students, the teacher can also facilitate it with google form; 4) At the data processing stage, the teacher invites students to communicate synchronously through zoom meetings or google meet; 5) At the proof stage, teachers and students also communicate synchronously through zoom meetings or google meet. This synchronous communication aims to verify the data that students find, 6) At the conclusion stage it is also done synchronously.